Effectiveness of lipid-lowering therapy in outpatients with coronary artery disease living in a large industrial center of Eastern Siberia - N. G. Gogolashvili; R. A. Yaskevich (Кардиоваскулярная терапия и профилактика)
Aim. To study the prescription rate of lipid-lowering therapy and achieving the target low-density lipoprotein cholesterol (LDL-C) values in outpatients with coronary artery disease (CAD) living in Krasnoyarsk.Material and methods. The study included all patients with CAD hospitalized in the cardiology department of the clinic of the Research Institute of Medical Problems of the North (Krasnoyarsk) in 2018-2019. The analysis included data from 1671 patients (men, 770; women, 901). During hospitalization, an in-depth survey of patients was carried out on the subject of prescribing and taking lipid-lowering drugs. On admission, lipid profile was assessed in all patients.Results. At the time of admission, only 51,4% of patients received lipidlowering therapy. The majority received statin monotherapy (99,2%). Only 0,8% of patients received combination therapy (statin+ezetimibe). The most frequently prescribed statin in the study was atorvastatin — 74,6%. Rosuvastatin was received by 17,1% of patients. In most cases, the doses of atorvastatin and rosuvastatin corresponded to the moderate-intensity statin therapy regimen. The frequently prescribed dose of atorvastatin was 20 mg/day — 54,4%, rosuvastatin — 10 mg/day — 68,7%. The target level of LDL-C <1,8 mmol/L was reached by 16,3%, <1,5 mmol/L — by 9,0%, <1,4 mmol/L — only 6,5% of patients. Most often, the target LDL-C levels were achieved by patients receiving high-intensity statin (HIS) therapy. The target level of LDL-C <1,8 mmol/L was reached by 37,5%, <1,5 mmol/L — 23,9%, LDL cholesterol <1,4 mmol/L — 20,7% of patients, receiving HIS.Conclusion. In patients with CAD living in Krasnoyarsk, the most commonly prescribed statins were atorvastatin and rosuvastatin, but only 32% of patients received HIS. Combination lipid-lowering therapy has been used extremely rarely. Among the surveyed patients, the current target level of LDL-C for patients with CAD (<1,4 mmol/L) was achieved only in 6,5% of patients. In the group of patients receiving high-intensity statin therapy, this target level was achieved in 20,7% of patients, which indicates the need for strict adherence to current clinical guidelines.